Self-Otherings and Reimaginings of Postcolonial African Women in Chimamanda Ngozi Adichie’s Americanah (2013) - Jauza Maryam Mumtazah; Lina Meilinawati Rahayu; Ari Jogaiswara Adipurwawidjana (Journal of Language and Literature, 2025)
Chimamanda Ngozi Adichie’s Americanah (2013) presents a narrative that shifts between different temporalities and spaces, a movement that is particularly experienced by its main character, Ifemelu, as she navigates through her Nigerian, American, and her newly found black identity. Similarly, the novel’s narrative attempts to showcase other postcolonial African women like Ifemelu, as well as their ambiguous identities and othered representations. Through this article, we examine the workings of Ifemelu’s narration as it shifts from one space to another, specifically from Nigeria to America and vice versa, through a narratological method. We will then focus on how these specific spaces occupied by Ifemelu and other African women, or what Ogundipe-Leslie calls “women’s spaces and modes, " work with the bodily experiences of the women and the black Atlantic world at large. Throughout the novel, the hair salon is the women’s space that the narration keeps returning to, serving as a bridge between the story’s past and present. However, a more constant form of women’s spaces also occurs through the narrative body itself, specifically through the narrative form of online blogs that showcase Ifemelu’s attempt to find familiarities with other black people of the diaspora. From this article’s analysis, we argue that the hair salon and the narration of the online blogs, as “micro-African” spaces, serve as mediums to reclaim and re-write the contingent and negotiated identities of postcolonial African in the new black Atlantic world.